Editorial - Hans-Uwe Otto (Social Work and Society)
The Collaborative Research Project"Making Capabilities Work" (WorkAble), funded by the EU within the Seventh Framework Programme, was initiated in response to the way in which a high level of youth unemployment has become a stable feature throughout Europe.Â  This feature is impacting on all countries without exception"”although varying in its degree. The situation is particularly dramatic when the youth unemployment rate is higher than that of all other employees. This has justifiably led to a public call for radical change"”a call always expressed with concern but sometimes also with aggression. It is not unjustified to talk about a lost generation, and this description applies particularly to southern and eastern European countries. However, alongside the contemporary situation, what we are really dealing with here is fundamental questions of justice that even the EU is now beginning to address in its official papers and policy statements.